Synaptic plasticity and spatial working memory are impaired in the CD mouse model of Williams-Beuren syndrome. Issue 1 (December 2016) - Borralleras, Cristina; Mato, Susana; Amédée, Thierry; Matute, Carlos; Mulle, Christophe; Pérez-Jurado, Luis; Campuzano, Victoria
Abstract Mice heterozygous for a complete deletion (CD) equivalent to the most common deletion found in individuals with Williams-Beuren syndrome (WBS) recapitulate relevant features of the neurocognitive phenotype, such as hypersociability, along with some neuroanatomical alterations in specific brain areas. However, the pathophysiological mechanisms underlying these phenotypes still remain largely unknown. We have studied the synaptic function and cognition in CD mice using hippocampal slices and a behavioral test sensitive to hippocampal function. We have found that long-term potentiation (LTP) elicited by theta burst stimulation (TBS) was significantly impaired in hippocampal field CA1 of CD animals. This deficit might be associated with the observed alterations in spatial working memory. However, we did not detect changes in presynaptic function, LTP induction mechanisms or AMPA and NMDA receptor function. Reduced levels of Brain-derived neurotrophic factor (BDNF) were present in the CA1-CA3 hippocampal region of CD mice, which could account for LTP deficits in these mice. Taken together, these results suggest a defect of CA1 synapses in CD mice to sustain synaptic strength after stimulation. These data represent the first description of synaptic functional deficits in CD mice and further highlights the utility of the CD model to study the mechanisms underlying the WBS neurocognitive profile.